Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/su13020994
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Effects of Nitrification Inhibitor DMPP on Acidification and Inorganic N Leaching Loss from Tea (Camellia sinensis L.) Cultivated Soils with Increasing Urea–N Rates

Abstract: The effects of nitrification inhibitor in tea gardens with different urea–N rates have rarely been assessed. For eight months, a glasshouse experiment was conducted to investigate the effects of a nitrification inhibitor (3, 4–dimethylpyrazole phosphate, DMPP) on the changes of soil pH and inorganic N loss. Urea (0, 300, 500, and 800 kg N ha−1) with or without DMPP (1% of urea–N applied) were added to pots that hosted six plants that were three years old. Next, three leaching events were conducted with 600 mL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 30 publications
1
7
0
1
Order By: Relevance
“…The reduction of N2O emissions by DMPP is therefore attributed to reduced nitrification process and a reduced NO3pool available in soil for denitrification (Ruser and Schulz, 2015;Suter et al, 2020). Thus, nitrification inhibitors are substances that delay the oxidation of NH4 + to NO3 -, preventing N losses through nitrification and denitrification (Luchibia, 2020;Qiao et al, 2021), as verified in our study. This delay maintains the applied N fertilizer in the less mobile form of NH4 + , and thereby limits the build-up of mobile NO3in the soil (Friedl., et al, 2017;Padilla et al, 2018).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The reduction of N2O emissions by DMPP is therefore attributed to reduced nitrification process and a reduced NO3pool available in soil for denitrification (Ruser and Schulz, 2015;Suter et al, 2020). Thus, nitrification inhibitors are substances that delay the oxidation of NH4 + to NO3 -, preventing N losses through nitrification and denitrification (Luchibia, 2020;Qiao et al, 2021), as verified in our study. This delay maintains the applied N fertilizer in the less mobile form of NH4 + , and thereby limits the build-up of mobile NO3in the soil (Friedl., et al, 2017;Padilla et al, 2018).…”
Section: Discussionsupporting
confidence: 77%
“…The DMPP is related to delay the oxidation of NH4 + to NO3thereby preventing N losses through nitrification and denitrification (Shi et al, 2016;Luchibia et al, 2020;Qiao et al, 2021). This delay maintains the applied N fertilizer in the less mobile form of NH4 + , limiting the buildup of mobile NO3in the soil (Friedl., et al, 2017;Padilla et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…+ for longer and alleviate soil acidification, Wang et al (2020) recommended that when fertilising with urea, urease and nitrification inhibitors are applied to limit N losses [46]. Qiao et al (2021) found that with the application of DMPP (3,4-dimethylpyrazole phosphate, a nitrification inhibitor), soil pH increased at a urea application rate of 500 kg N ha −1 and above, due to reduced nitrification and increased plant uptake of NO 3 − [86]. The leaching losses of nitrates and total inorganic N were also noticed to decrease with the addition of DMPP.…”
Section: Intercropping With Legumesmentioning
confidence: 99%
“…The DMPP treatment seemed to stimulate CH4 oxidation more than DCD treatment because the soil clearly acted as a CH4 sink rather than as a source [50]. Significant reduction due to inhibition of nitrification may take more than a week after DMPP addition [59]. DMPP could increase soil N retention, improve plant N use efficiency, and potentially stimulate the shoot yield of tea trees [59].…”
Section: -4 Dimethylpyrazole Phosphatementioning
confidence: 99%